Analysis of Temperature Characteristics of Electrolytic-Plasma Discharge in Jet Processing of a Metal Anode - A. I. Popov; V. I. Novikov; D. N. Ivanov; I. A. Kozyrskiy (Advanced Engineering Research, 2025)
Introduction. Electrolytic plasma technologies used for dimensional and finishing processing of metal surfaces attract attention due to their high efficiency and precision. The key factor that determines the quality of processing is the temperature of the electrolytic-plasma discharge (EPD), which affects the ionization of the electrolyte and the properties of the surface. The lack of comprehensive studies of the temperature characteristics of jet EPD limits the optimization of processes. The research objective is to determine the distribution of temperatures and heat flows in the system “jet electrolytic cathode — metal anode” under various processing conditions.Materials and Methods. The study was conducted using an electrolyte jet with a diameter of 3 mm and a mass flow rate of 0.25–3.75 g/s at a voltage of 20–500 V. KhVG and 08Kh18N9T steels were used as anodes, and the electrolytes were aqueous solutions of NaCl, (NH4)2SO4, C6H8O7, with a concentration of 4–50 g/l. The temperature was measured with a chromel-alumel thermocouple, an infrared pyrometer, and a thermal imager.Results. A heat balance equation was developed, describing heat distribution among the metallic anode (MA), jet cathode, electrolyte, vapor, and radiation. The analysis of the volt-ampere characteristics (VAC) showed an increase in current at low electrolyte flow rates (0.75–1.2 g/s) followed by a decrease at 300–500 V, and a parabolic dependence with a maximum of 2.6 A at a flow rate of 2.37 g/s. The maximum MA temperature reached 100°С (NaCl, 4–35 g/L), decreasing to 82°С at 150 g/L, while the hollow cathode reached 158°С at an initial electrolyte temperature of 90°С. Vapor temperatures ranged from 67.3°С (high flow rates) to 87.5°С (low flow rates). Electrolyte loss due to evaporation reached 5,8 g at 300–340 The temperature at the periphery of the anode was 15–20% higher than in the center.Discussion and Conclusion. The main source of heat was the Joule-Lenz law, with the contribution of exothermic reactions of carbon oxidation up to 260 V. The maximum heat release was observed in the EPD zone, forming an ellipsoid. The data obtained and the heat balance equation create the basis for optimizing jet electrolytic-plasma polishing in mechanical engineering, medicine, and microelectronics.